Safeguarding Cultural Identity: The Role of the Indonesian Language amid Globalization - Sugiarti Sugiarti; Vella Julia (Smart Society, 2025)
Globalization has significantly impacted various aspects of human life, particularly in the cultural sphere, where local traditions and values face the threat of erosion due to the widespread influence of foreign cultures. In this context, the Indonesian language plays a vital role not only as a national unifying tool but also as a strategic medium for preserving and transmitting local cultural identity. This study aims to analyze the functions of the Indonesian language in preserving local cultural identity amid the challenges posed by globalization. Employing a descriptive qualitative approach through an extensive literature review, the research highlights the multifaceted role of the Indonesian language. It is not merely a means of communication, but also a carrier of local wisdom expressed through literary works, educational content, media discourse, and oral traditions that reflect the nation's cultural richness. The findings emphasize the importance of strengthening the use of the Indonesian language in everyday life and formal settings, particularly in ways that are rooted in local values and knowledge systems. This study underscores the need for collective awareness and national commitment to protect the Indonesian language as a symbol of identity and a cultural safeguard. It contributes to scholarly discussions on language policy, cultural resilience, and identity preservation in an increasingly globalized world.